2022
DOI: 10.3389/fphar.2022.834948
|View full text |Cite
|
Sign up to set email alerts
|

S1PR3, as a Core Protein Related to Ischemic Stroke, is Involved in the Regulation of Blood–Brain Barrier Damage

Abstract: Background: Ischemic stroke is the most common stroke incident. Sphingosine-1-phosphate (S1P) receptor 3 (S1PR3) is a member of the downstream G protein-coupled receptor family of S1P. The effect of S1PR3 on ischemic stroke remains elusive.Methods: We downloaded two middle cerebral artery occlusion (MCAO) microarray datasets from the Gene Expression Omnibus (GEO) database and screened differentially expressed genes (DEGs). Then, we performed a weighted gene coexpression network analysis (WGCNA) and identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
1
1
0
Order By: Relevance
“…Ischemic injury causes an increase of AQP4 expression perivascular astrocyte swelling . It has been demonstrated that, after MCAO, the AQP4 protein level was upregulated, and expanded around the blood vessels in the mouse brain, and our results also confirmed a similar trend of AQP4 after ischemic injury in the present study. Therefore, LAQ treatment reduced the increased expression of AQP4, indicating that the neuroprotective effect of LAQ may be involved in the downregulation and redistribution of AQP4.…”
Section: Discussionsupporting
confidence: 91%
“…Ischemic injury causes an increase of AQP4 expression perivascular astrocyte swelling . It has been demonstrated that, after MCAO, the AQP4 protein level was upregulated, and expanded around the blood vessels in the mouse brain, and our results also confirmed a similar trend of AQP4 after ischemic injury in the present study. Therefore, LAQ treatment reduced the increased expression of AQP4, indicating that the neuroprotective effect of LAQ may be involved in the downregulation and redistribution of AQP4.…”
Section: Discussionsupporting
confidence: 91%
“…For the first time to our knowledge, this study provides evidence of higher S1PR3 plasma levels in murine and human ischemic stroke and thus, supports findings obtained in a proteomic assessment of peripheral blood mononuclear cells (PBMCs) that identified S1PR3 as one of 146 core genes potentially related to ischemic stroke. 68 Using receiver operating characteristic (ROC) analysis, the authors suggested S1PR3 as good ischemic stroke indicator. 68 However, care must be taken when interpreting and generalizing these findings because of their small sample size (i.e., 20 stroke patients and 20 control subjects) without available information on sampling timepoint post-stroke, stroke severity or sex of the participating subjects.…”
Section: Discussionmentioning
confidence: 99%
“… 68 Using receiver operating characteristic (ROC) analysis, the authors suggested S1PR3 as good ischemic stroke indicator. 68 However, care must be taken when interpreting and generalizing these findings because of their small sample size (i.e., 20 stroke patients and 20 control subjects) without available information on sampling timepoint post-stroke, stroke severity or sex of the participating subjects. Although high S1PR3 levels in patients with acute stroke were not associated with neurological impairment, worse general outcome, or inflammation in our study, S1PR3 signaling may still be an interesting target to consider for further stroke therapy studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to acting as a protective factor in neurodegenerative disease, activation of NRF2 also ameliorates damage caused from ischemic stroke where it protects the BBB, improves edema, and mitigates neurological defects by reducing oxidative stress (69,72). It is also likely that NRF2 activation restricts the overactivation of type I IFN by microglia which occurs during the acute phase of stroke with deleterious consequences (73).…”
Section: Discussionmentioning
confidence: 99%